CADASTRE OF CAVES IN ROMANIA - LEGAL ASPECTS (PANGEEA, 2025)
The development of caves takes place naturally underground, but the lands above the caves are also involved. That is why there is a need to represent them on cadastral plans: both underground and on the surface through the horizontal projection of the naturally created gaps (above the cave) to establish the protected area;
Keywords: cave; protected areas; horizontal projection of naturally created gaps